2022
DOI: 10.1039/d2an01172g
|View full text |Cite
|
Sign up to set email alerts
|

Quantification anomalies in single pulse LA-ICP-MS analysis associated with laser fluence and beam size

Abstract: Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has undergone major improvements in recent years which have led to reduction of the analysis time, higher spatial resolution, and better sensitivity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Selective ablation of the gelatin microdroplets and tissue sections was achieved by selecting an energy density below the ablation threshold of glass and above the ablation threshold of gelatin . Gelatin microdroplets and tissue sections were removed quantitatively using a fluence of 0.60 J cm –2 …”
Section: Methodsmentioning
confidence: 99%
“…Selective ablation of the gelatin microdroplets and tissue sections was achieved by selecting an energy density below the ablation threshold of glass and above the ablation threshold of gelatin . Gelatin microdroplets and tissue sections were removed quantitatively using a fluence of 0.60 J cm –2 …”
Section: Methodsmentioning
confidence: 99%
“…Ionisation of Cu and Zn in solution resulted in the formation of [M(NO 3 ) x (H 2 O) y (OH) z ] + complex ions in the MPT. These ions were then subject to MS 4 multi-stage fragmentation using CID to obtain the ions 63 Cu + and 66 Zn + which yielded LODs of 0.23 and 1.1 mg L −1 , respectively.…”
Section: Instrumentationmentioning
confidence: 99%
“…Additional uncertainties associated with laser fluence and beam size using various ablation cells and interfaces make quantification even more challenging. These additional factors are considered by Jerse et al 63 using approaches based on pulse intensity, LA spot volumes and noise characteristics for As, Gd, La, Ni, Te and Zn. A range of analyte concentrations (between 10 and 1000 μg g −1 ), and matrices (gelatine standards and NIST SRM 612) were studied.…”
Section: Solids Analysismentioning
confidence: 99%
“…4, it could be found that the analytical precision of Cr and Cd is poorer than that of Pb. In addition to the relatively low signal-to-noise ratio of these two elements, some studies have also pointed out that it may be affected by the carbon loading in the ICP and ablated particle size, 41,42 resulting in uctuations and nonlinear shis in the signal intensity in the long-term analysis. 43 This eventually resulted in measured RSD values of 1.5%, 3%, and 2.5% for Pb, Cd, and Cr elements, respectively.…”
Section: Evaluation Of Homogeneity By La-icp-msmentioning
confidence: 99%